Violencia y resistencia en la voces emergentes de América Latina: Las chicas muertas de Selva Almada (Altre Modernità, 2019)
This article attempts to contribute to the study of the relationship between literature and human rights by focusing the analysis on the representation of femicide – universal issue that persists in today's Latin American and global society – in the latest Spanish-American narrative. In particular, I intend to investigate the relationship between violence and resistance, reality and fiction, literature and human rights, based on the analysis of Chicas muertas (2015), a recent novel by the Argentinian writer Selva Almada (1973), representative of a young generation of Latin American voices that are bearing witness to a verbal, psychological and physical violence, that is extreme and new in its crudeness.